2016
DOI: 10.1074/jbc.m116.719302
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Protein IκBζ Forms a Transcriptionally Active Complex with Nuclear Factor-κB (NF-κB) p50 and the Lcn2 Promoter via the N- and C-terminal Ankyrin Repeat Motifs

Abstract: The nuclear protein IB, comprising the N-terminal transactivation domain and the C-terminal ankyrin repeat (ANK) domain composed of seven ANK motifs, activates transcription of a subset of nuclear factor-B (NF-B)-dependent innate immune genes such as Lcn2 encoding the antibacterial protein lipocalin-2. Lcn2 activation requires formation of a complex containing IB and NF-B p50, a transcription factor that harbors the DNA-binding Rel homology region but lacks a transactivation domain, on the promoter with the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…However, the molecular mechanism of IκBζ‐mediated regulation on the NF‐κB–dependent IL‐36γ expression remains elusive. The cytoplasmic IκBζ members such as IκBα and IκBβ are negative regulators of NF‐κB activation and nuclear translocation, while nuclear IκBζ functions quite differently in the regulation of NF‐κB . In our study, we found that the p65 phosphorylation in response to poly(I:C)/IL‐17A was not significantly changed by IκBζ knockdown (data not shown), which were consistent with previous analyses showing that NF‐κB activation was not affected in macrophages from IκBζ‐deficient mice .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the molecular mechanism of IκBζ‐mediated regulation on the NF‐κB–dependent IL‐36γ expression remains elusive. The cytoplasmic IκBζ members such as IκBα and IκBβ are negative regulators of NF‐κB activation and nuclear translocation, while nuclear IκBζ functions quite differently in the regulation of NF‐κB . In our study, we found that the p65 phosphorylation in response to poly(I:C)/IL‐17A was not significantly changed by IκBζ knockdown (data not shown), which were consistent with previous analyses showing that NF‐κB activation was not affected in macrophages from IκBζ‐deficient mice .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that the p65 phosphorylation in response to poly(I:C)/IL‐17A was not significantly changed by IκBζ knockdown (data not shown), which were consistent with previous analyses showing that NF‐κB activation was not affected in macrophages from IκBζ‐deficient mice . It was reported that IκBζ activates the expression of LCN2 by forming a regulatory complex with NF‐κB and LCN2 promoter DNA . Therefore, we postulated that the NF‐κB–dependent induction of IκBζ subsequently enhances the NF‐κB binding to the IL‐36γ promoter as a positive feedback mechanism.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Ankyrin G vaccination is tested for the reduction of Aβ and lowering toxicity ( Santuccione et al, 2013 ). Ankyrin repeats are interaction sites of phosphorylation dependent dynamic assembly of proteins and nucleic acids ( Hall et al, 2018 ) including those involved in transcription regulation ( Kohda et al, 2016 ) and signaling, and present promising targets for the design of new drugs.…”
Section: Discussionmentioning
confidence: 99%